PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN PENGENDALIAN INTERNAL: STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Anis Naseha; Ataina Hudayati (Fakultas Ekonomi Universitas Pekalongan, 2020)
This study aims to examine the effect of corporate governance on disclosure of internal controls. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The sampling method in this study was purposive sampling. Quantitative analysis method consists of validity test, correlation test, classical assumption test. Hypothesis testing using panel data regression method using E-Views. The results of this study indicate that ownership concentration has a significant effect on disclosure of internal control, while the independence of the board of directors, board size, and institutional ownership does not significantly influence. Keywords: Corporate Governance and Internal Control Disclosures